Emerging Strains in GCC Labor Markets - Fasano-Filho, Ugo (IMF Working Papers; Working Paper ;, 2004)
Unemployment pressures among nationals are emerging in the Cooperation Council for the Arab States of the Gulf (GCC). 2 At a time when a rapidly growing number of young nationals are entering the labor force and governments are no longer able to act as employers of first and last resort, the non-oil sector continues to rely on expatriate labor to meet its labor requirements in most GCC countries. In this environment, policymakers face the related challenges of addressing unemployment pressures while striking a balance between maintaining a liberal foreign labor policy and a reasonable level of competitiveness of the non-oil sector. Using a matching function framework, this paper examines labor market policies that are likely to expand the ability to hire nationals in the non-oil sector. It finds that an effective labor strategy should focus on strengthening investment in human capital, adopting institutional reforms, and promoting a vibrant non-oil economy.